The Relationship between Reading Self-Efficacy, Reading Attitude and EFL Reading Comprehension Based on Gender Difference - Rachmajanti, Sri; Musthofiyah, Uning (Journal of English Language, Literature, and Teaching (J-ELLiT), 2017)
Literacy has been of vital importance in learning in a foreign language, and lots of research have been conducted to investigate the importance of reading comprehension; however, studies on this dealing with gender are limited. Therefore, the purpose of the study is to examine the relationship among reading attitude, reading self-efficacy and reading comprehension of EFL tertiary students based on gender difference. A convenient sampling is used to draw data from 208 respondents ranging form the age of 19 to 24 years old using questionnaires and a reading comprehension test. This is a correlational study (Creswell, 2008) employing a multi-group path analysis. The result of analysis showed a pattern of relationships based on gender difference among reading attitude, reading self-efficacy and reading comprehension. The study has significant impacts for EFL reading comprehension by showing prediction of EFL reading comprehension achievement from reading self-efficacy and reading attitude on the basis of gender difference.Â